1) x+4=28
x=28-4
x=24
24+4=28
2)y-6.5=31
y=31+6.5
y=37.5
37.5-6.5= 31
03) 8z= 40 + 3Z
8Z - 3Z= 40
5Z=40
Z=40:5
Z=8
04) 10X = -5X + 60
10X + 5X = 60
15X=60
X=60 : 15
X=4
05) -15Y + 3= - 36 - 18Y
-15Y + 18Y = -36 -3
3Y= -39
Y= -13
06)2X + 4 + (3X- 4) = 3X + 12
5X = 3X + 12
5X - 3X= 12
2X=12
X=6
07)4(3x + 2) - 8 = 5(2x+3) + 5
12x + 8 - 8 = 10x + 15 + 5
12x - 10x = 20
2x = 20
x = 10
08)15x - 40 - 5x -20 = 0
10x -60 = 0
10x= 60
x=6
09) 16 - (-2x - 4) - (5x - 3x + 2) = - 4x - ( - 8x + 2)
16 + 2x + 4 - 5x + 3x -2 = - 4x +8x - 2
2x -5x + 3x + 4x -8x = -2 -16 -4 +2
- 4x = -20
x= -20 : -4
x=5
10) - (7x - 2 + 12) + ( - 5x - 3x + 4) = - ( - x + 7) - (6x - 4 - 7)
-7x + 2 - 12 - 5x -3x + 4 = x - 7 - 6x + 4 + 7
2 -12 + 4 - 4 = x - 6x + 7x + 5x + 3x
-10 = 10x
x= -1
11) - 18 - [ 3(x + 2) + 4] = 21 - [ 6( - 2x - 2) + 1]
- 18 - [ 3x+ 6 + 4]= 21 - [ - 12x - 12 + 1]
-18 - [3x+10]= 21 - [ - 12x - 11]
-18 - 3x - 10 = 21 + 12x + 11
-10 -21 -11 - 18= 12x +3x
- 60 = 15x
x = - 4
03) 8z= 40 + 3Z
8Z - 3Z= 40
5Z=40
Z=40:5
Z=8
04) 10X = -5X + 60
10X + 5X = 60
15X=60
X=60 : 15
X=4
05) -15Y + 3= - 36 - 18Y
-15Y + 18Y = -36 -3
3Y= -39
Y= -13
06)2X + 4 + (3X- 4) = 3X + 12
5X = 3X + 12
5X - 3X= 12
2X=12
X=6
07)4(3x + 2) - 8 = 5(2x+3) + 5
12x + 8 - 8 = 10x + 15 + 5
12x - 10x = 20
2x = 20
x = 10
08)15x - 40 - 5x -20 = 0
10x -60 = 0
10x= 60
x=6
09) 16 - (-2x - 4) - (5x - 3x + 2) = - 4x - ( - 8x + 2)
16 + 2x + 4 - 5x + 3x -2 = - 4x +8x - 2
2x -5x + 3x + 4x -8x = -2 -16 -4 +2
- 4x = -20
x= -20 : -4
x=5
10) - (7x - 2 + 12) + ( - 5x - 3x + 4) = - ( - x + 7) - (6x - 4 - 7)
-7x + 2 - 12 - 5x -3x + 4 = x - 7 - 6x + 4 + 7
2 -12 + 4 - 4 = x - 6x + 7x + 5x + 3x
-10 = 10x
x= -1
11) - 18 - [ 3(x + 2) + 4] = 21 - [ 6( - 2x - 2) + 1]
- 18 - [ 3x+ 6 + 4]= 21 - [ - 12x - 12 + 1]
-18 - [3x+10]= 21 - [ - 12x - 11]
-18 - 3x - 10 = 21 + 12x + 11
-10 -21 -11 - 18= 12x +3x
- 60 = 15x
x = - 4
No hay comentarios:
Publicar un comentario